Pengaruh Tepung Daging Kijing Air Tawar Sebagai Substitusi Tepung Ikan Terhadap Pertumbuhan Ikan Lele Sangkuriang (Clarias gariepinus var) - Hamron, Novita; Hety Novitasari; Bambang Wijaya Kesuma; Ratih Dwi Padmadi (Fakultas Pertanian, 2025)
Kijing Meat Flour has the potential to be a good source of nutrients for fish because of its high protein content and also contains fats, minerals that can promote fish growth and health. This study aims to determine the effect of giving freshwater kijing meat flour as a substitute for fish meal in fish feed formulation to increase the growth of sangkuriang catfish (Clarias gariepinus var). This study used a Complete Random Design (RAL) with 4 treatments and 4 replicates consisting of 16 units. The treatment includes: Treatment A: Kijing meat flour 0%+anchovy head flour 65%+corn flour 30%+vitamin 5%, Treatment B: Kijing meat flour 45%+anchovy head flour 30%+corn flour 20%+vitamin 5%, Treatment C: Kijing meat flour 55%+anchovy head flour 25%+corn flour 5%+vitamin 5%, Treatment D: Kijing meat flour 65%+anchovy head flour 20%+Corn flour 10%+vitamin 5%. The results showed that Treatment C: kijing meat flour 55% + anchovy head flour 25% + corn flour 5% + vitamin 5% produced the best growth of sangkuriang catfish with an absolute length value of 6.33cm, absolute weight growth of 14.23g, survival of 93.03% and feed conversion of 0.72%.